ANALISIS BIAYA DAN WAKTU PADA PEMBANGUNAN GEDUNG GRAHA CK - Muhammad Nafhan Isfahani (FTSP Universitas Jayabaya, 2020)
The concept of earned value is one of the tools used in managing the Graha CK development that integrates cost and time. The concept of earned value presents three dimensions, namely the physical completion of the project that reflects the planned absorption of costs, the actual costs that have been incurred or called the actual costs and what is obtained from the costs that have been incurred or called earned value The purpose of cost and time control analysis in the Graha CK building construction project is to obtain ACWP, BCWS, BCWP on the Graha CK Building construction project, obtain SPI, CPI on the Graha CK Building construction project, obtain ECD, EAC on the Graha CK Building construction project. From the results of the analysis using the earned value concept method to control the cost of the Graha CK building construction project, the results obtained were BCWS 950,338,876, BCWP 984,565,1162, ACWP produced 1,107,128,740,000. SPI 1.04, CPI 0.89. EAC produced 2,080,103,679 and ECD produced 13.72 months.